Analysis of the efficiency of sludge dewatering using Moringa oleifera as natural phytocoagulant - Abdulazeez, Qabas Marwan; Jami, Mohammed Saedi; Alam, Md. Zahangir; Iwata, Masashi (2015)
In order to evaluate the efficiency of sludge dewatering, specific parameters such as settling velocity (Vs) and sludge volume index (SVI) have to be measured. However, problems arise when these parameters are used for the evaluation of efficiency using M. oleifera as natural phytocoagulant or sludge conditioner. Using statistical optimization, it was found that despite good results of Vs and SVI, the concentration of residual suspended solids in supernatant liquid or turbidity was very high. Thus, turbidity of supernatant liquid was selected as a criteria to evaluate the efficiency of dewatering process. In this research, two optimization steps were run under two factors for each optimization; i.e., mixing time and concentration of M. oleifera seeds extract with NaCl (1 M). The range of these factors was (100 – 1000 mg/L) for M. oleifera seeds extract concentration, and (5 – 30 min) for mixing time. In the first optimization, Vs and turbidity were used as responses. While in the second optimization SVI and turbidity were used as response parameters. Both optimization steps were run under (pH = 7), mixing speed (120 rpm) for the first minute, and (40 rpm) during the rest period of experiment. By using Design-Expert software v9, for the first optimization of settling velocity, the optimum Vs was found to be (1 cm/min) and the turbidity of the supernatant was (350.7 NTU). Whereas in the optimization of the sludge volume index (SVI), the optimum value was (24.7 mL/g), corresponding turbidity value of suspended solids in supernatant liquid was (341.5 NTU). Since the turbidity was very high, second optimization by redesigning the factors was conducted resulting in optimum values of dosage of (462.8 mg/L), mixing time of (13.4 min), turbidity of (67.2 NTU) (further (80.2 %) reduction compared to the (350.7 NTU) of the first optimization) and settling velocity of (0.93 cm/min) were obtained. For the optimization of SVI, dosage of (447.5 mg/L) and mixing time of (8.3 min) gave (33.5 mL/g) of SVI with (67.2 NTU). These optimized dewatering parameters can be used to improve the efficiency of sludge dewatering.